Primary Teachers’ Perspectives on Using Artificial Intelligence Technology in English as a Second Language Teaching and Learning: A Systematic Review - Zulkarnain, Nur Sakinah; Md Yunus, Melor (International Journal of Academic Research in Progressive Education and Development, 2023)
Artificial Intelligence in Education (AIEd) is an emerging education field. This paper explicitly investigates the use of AI technology in language learning specifically in English as a Second Language (ESL). As a robust cloud-computing solution, AI-powered technology can be used to aid teaching and learning processes and improve language learning. While students' perspectives on AI-related research are prevalent, teachers' perspectives are not extensively discussed. In addition, studies on the effects of AI technology in ESL primary education, are understudied. Using two databases, namely Google Scholar and the Educational Resources Information Centre (ERIC), 12 articles related to the use of AI technology in ESL teaching and learning in primary schools were extracted out of 672, from 2019 to 2022 by using the PRISMA review methodology. Teachers’ perspectives were discussed based on the effectiveness, convenience, motivation and challenges. It is found that teachers perceived the integration of AI technology positively due to its dynamic characteristics and effectiveness despite facing various challenges resulting in disadvantages associated with its use. This paper explores AI technology's impact on ESL primary education from the perspective of teachers as curriculum stakeholders. Future research should delve further into the challenges that impede the use of AI technology in ESL primary education. This is essential for sustaining the momentum of AI-powered education.